2021
DOI: 10.1007/s00264-021-05193-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results after very early, early and late arthroscopic arthrolysis of the knee

Abstract: Purpose Impaired patient outcome can be directly related to a loss of motion of the knee following surgical procedures. If conservative therapy fails, arthroscopic arthrolysis is an effective procedure to improve range of motion (ROM). The purpose of this study was to evaluate the outcome of patients undergoing very early (< 3 months), early (3 to 6 months), and late (> 6 months) arthroscopic arthrolysis of the knee. Methods With a follow-up on avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In comparison to a recently published systematic review [ 9 ], the rate of LOA was higher in our study as the indication for early LOA was made generous in this study. This decision was based on a recent study that revealed significantly improved range of motion and functional scores of early LOA (within 6 month) compared to late LOA (> 6 month) [ 7 ]. Although a postoperative flexion deficit of 10–15° has been reported before [ 27 ], a more progressive rehabilitation with unlimited range of motion may be necessary in future rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to a recently published systematic review [ 9 ], the rate of LOA was higher in our study as the indication for early LOA was made generous in this study. This decision was based on a recent study that revealed significantly improved range of motion and functional scores of early LOA (within 6 month) compared to late LOA (> 6 month) [ 7 ]. Although a postoperative flexion deficit of 10–15° has been reported before [ 27 ], a more progressive rehabilitation with unlimited range of motion may be necessary in future rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…There are different studies on literature on the efficacy of arthroscopic releases in stiff knee, with good outcomes (60,61,62). Particularly, a recent study from Eggeling et al (63) compared mid-term results between very early (<3 months), early (3-6 months) and late (>6 months) arthroscopic release after surgical procedures to treat postoperative knee stiffness. The final ROM after arthrolysis was significantly increased in the group of very early and early arthrolysis while postoperative flexion deficit was higher in the late group.…”
Section: Arthroscopic Releasementioning
confidence: 99%